Halal Economic Ecosystem of Indonesia and Thailand through Halal Certification Bodies (BPJPH & CICOT): Ekosistem Ekonomi Halal di Indonesia dan Thailand melalui Lembaga Sertifikasi Halal (BPJPH & CICOT) - Jannah, Muti’ah Nurul; Suryani, Suryani; Syarifudin, Efi (Al Dzahab, 2025)
Purpose: This study aims to analyze the halal economic ecosystem in Indonesia and Thailand through the role of halal certification bodies, namely BPJPH (Halal Product Assurance Organizing Agency) in Indonesia and CICOT (Central Islamic Council of Thailand) in Thailand. Design/methodology/approach: Using a qualitative descriptive research method, this study examines how both countries develop the halal economic ecosystem through aspects of demand, government support, and the availability of halal products. Findings: The results indicate the growth of the halal economic ecosystem, which requires approaches in terms of demand, support, and supply. Research implications: The growing Muslim population drives the increasing demand. The establishment of BPJPH (Halal Product Assurance Organizing Agency) in Indonesia and CICOT (Central Islamic Council of Thailand) illustrates the government’s support for developing the halal economic ecosystem in Indonesia and Thailand. Lastly, the collaboration between Indonesia and Thailand serves as an additional effort to advance the global halal economic ecosystem.